pengaruh penerapan efiling terhadap kepatuhan wajib pajak dalam menyampaikan SPT tahunan dengan kepuasan kualitas pelayanan sebagai variabel intervening - Rita Ratna sari; Teguh Erawati (Jurnal Akuntansi, 2018)
This study aims to analyze the effect of efficacy against Taxpayer Compliance with service quality as intervening variable in Gunungkidul Region.This research data is obtained from questionnaire (Primer) which is distributed to the Taxpayer using efiling program in Gunungkidul area. The population of this study is Individual Taxpayers who use efiling in the area of gunungkidul. The sample used in this study were 70 respondents. This research uses analytical path. The results of this study indicate that (1) Application of E-Filling System has a significant effect on service quality satisfaction. This is proven through simple linear regression analysis obtained by R Square value of 0.791, which can be interpreted that the effect of E-Filling System Implementation on Taxpayer Compliance is 79.1%. The result of the statistical t test yields a significance value smaller than the significant level of 0.000 <0.05.(2) satisfaction of service quality have a significant effect to taxpayer compliance this is proven through simple linear regression analysis obtained R Square value equal to 0,501 which can be interpreted that the influence of satisfaction of service quality to Taxpayer Compliance is 50,1%. The result of the statistical t test yields a significance value smaller than the significant level of 0.000 <0.05. (3) the application of efiling affect taxpayer compliance significantly influence taxpayer compliance. This is evidenced through simple linear regression analysis obtained R Square value of 0.462 which means that the efiling program to the satisfaction of service quality 46,2%. The result of the statistical t test yields a significance value smaller than the significant level of 0.000 <0.05(4) efiling program has an effect on compliance through service quality. This is proven through simple linear regression analysis obtained R Square value of 0.560 This shows the efiling program affect taxpayer compliance through service quality satisfaction of 56.0% The result of the statistical t test yields a significance value smaller than the significant level of 0.000 <0.05.